In-vitro α-glucosidase inhibitory activity of the formulated capsules from the ethanolic extract of petersianthus quadrialatus (merr) merr - Dayao, Christian Tony J.; Mendeja, Brian Miles Z.; Song, Kyla Khristina S.; Balotro, Buenvenido S. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Aiming to address the rising burden of diabetes, this formulation research explored Petersianthus quadrialatus (Toog) as a natural α-glucosidase inhibitory agent. Given the promising therapeutic potential of indigenous plants, the study aimed to develop a Petersianthus quadrialatus capsule to aid in its development as a herbal supplement. The study builds on the research of Balotro, Yu & Quibin in 2016 by adapting their original research design and modifying their methodological approach. The leaves of Petersianthus quadrialatus were collected from an arboretum in Davao, shipped to Manila, garbled, and milled into powdered form. These milled leaves were processed and concentrated to yield two forms of extracts– (1) Petersanthus quadrialatus with chlorophyll, and (2) Peterisanthus quadrialatus chlorophyll-removed. The leaves and extracts were monitored through pharmacopeial tests, phytochemical screening, and thin layer chromatography. Pre-formulation studies involving hygroscopicity, stability, & compatibility were performed to assess the stability of the extracts and the compatibility of varied P. quadrialatus with chlorophyll extract & excipient combinations through different light, temperature, and relative humidity conditions. The capsule formulation trials containing the Petersianthus quadrialatus extracts as the active ingredient, combined with the compatible excipients yielded promising quality control results in powder flowability, weight variation, moisture content, and disintegration. The in-vitro α-glucosidase inhibitory activity of the Petersianthus quadrialatus extracts along with their respective formulations were also determined in-house and through contract laboratory testing services. The results of the in-house assay did not establish any inhibitory effect, while the serviced testing was able to exhibit significant inhibitory activity against α-glucosidase.
available to general public
Keywords: Plant extracts. -- Therapeutic Uses -- In vitro; Petersianthus quadrialatus; .; Alpha-glucosidase inhibition assay capsule formulation; Stability and compatibility studies